Evolutionary history and connectivity of the main river basin of the atlantic forest domain - Oliveira Júnior, Neil Damas de (2019)
The Atlantic Forest is one of the biodiversity hotspots in the world and includes the Doce River Basin one of the largest basins in the Atlantic domain. Important economic activities are not developed in the Rio Doce basin such as agriculture, livestock production and mining, contributing to the fragmentation of the landscape and threatening local diversity. In November 2015, the disruption of the Fundão dam in the district of Bento Rodrigues in Mariana caused the biggest disaster with the mining dam of history, releasing more than 40 million cubic meters of tailings of iron beneficiation. Terrestrial ecosystems suffered strong biomass losses, mainly in the valley funds between the Fundão Dam and the Candonga hydroelectric power plant. In 2017, 15 are mining dams were unstable in the state of Minas Gerais, threatening the local biodiversity that is the source of ecosystem functions and services, and the productivity of an ecosystem that is commonly related to the increase in Species richness. However, measurements of wealth or biological diversity are not accurate regarding the amount of ecosystem services existing in a community. Broad approaches such as phylogenetic diversity, functional diversity and landscape ecology are important tools for measuring ecosystem functions, especially productivity. The main objective of this dissertation was to know the evolutionary history of tree plant species in the Rio Doce Basin and to understand the structure and the assembly of communities in tropical forests through an evolutionary approach involving the phylogenetic metrics and environmental variables and to know the current connectivity panorama of fragments in the basin, identifying areas with great resistance to connectivity that should receive efforts to reestablish connectivity. To evaluate the phylogenetic potential, the different phylogenetic metrics (Faith index (FI) or PD, mean pairwise Distance (MPD) and mean Nearest taxon Index (MNT)) were analyzed, as well as their standardized measures for the effect of wealth (SESPD, SESMPD and SESMNTD). In addition, the evolutionary distinctiveness Index (ED) used to identify clades with unique evolutionary characteristics was calculated. To evaluate the relation of phylogenetic metrics and climatic variables of soil and climate was used the analysis Generalized Least Squares (GLS) Finally, the phylogenetic turnover measures (e.g. philobetadiversity) were analyzed to measure the degree of relationship among species along the basin. The current panorama of basin connectivity was evaluated using GIS software and the Linkage Mapper plug in for testing models of landscape resistance to connectivity, generating maps that illustrate the current functional connectivity of the Doce River basin and support conservation plans. Our results from the first chapter suggest that environmental and geographic variables affect the phylogenetic structure of plant communities in the Doce river basin, which were explained mainly by soil and climatic variables related to relations Soil water and precipitation, suggesting an evolution in seasonally demarcated conditions. The analysis of Philobetadiversity showed that there is a significant relationship between the lineages and geographic, topographic and environmental variables of the Doce river basin, suggesting a tendency of phylogenetic grouping in the higher portions of the basin Suggesting niche conservantism as a result of large selective pressures in these portions of the basin. The results of the second chapter show that despite being heavily fragmented, the Doce River basin still has functional connectivity mainly in the western portion. The center-north of the basin comprising the region of Governador Valadares is the region with the highest resistance to connectivity, a result of strong anthropic pressures that reduced forest remnants, requiring intervention through projects of Degraded area recovery to avoid loss of biodiversity due to lack of connectivity. In addition, recovery projects of degraded areas should also be developed in the region of Linhares that also presented resistance to connectivity and is included in the Central corridor of the Atlantic Forest, a region rich in biodiversity with high endemism and high number of endangered species, therefore it is essential to keep it in order to maintenance of biodiversity.